A Review on Herbal Medicinal Plant for Treatment of Polycystic Ovarian Syndrome (PCOS) - Yadav, Karishma; Ghadge, Priyanka; Langeh, Aryan; Kalbhare, Shankar; Phadtare, Prajkta; Bhoite, Rupali (Asian Journal of Pharmaceutical Research and Development, 2020)
Infertility due to polycystic ovarian syndrome (PCOS) is a worldwide problem that is increasing at alarming rates. It is characterized by chronic anovulation, polycystic ovaries, and hyperandrogenism leading to symptoms of irregular menstrual cycles, hirsutism, acne and infertility. Insulin resistance and elevated levels of male hormones (androgens) are associated with PCOS. The sedentary lifestyle, lack of exercise and dietary variations and stress etc., are also the contributory factors. Various plants like Panax ginseng, Punica granatum, Curcuma longa, Cinnamomum zeylanicum Tribulus terrestris, Symplocos racemosa, Trigonella foenum-graecum, Cocus nucifera etc., proved active in the treatment of PCOS. In this review, attempts have been made to summarize the important medicinal plants which are used in treatment or prevention of PCOS. Special attention is given to the role of insulin resistance and the potential utility of insulin sensitizers in management of PCOS.